The avatars of military education in New Granada (1820-1855) (2018)
From the beginning of the formation of the nation state in Colombia, the men associated with the use of arms made efforts to establish a school to contribute to the professionalization of oficers for the army. Notwithstanding, over the following decades, although different bills were passed and a Military School was founded (1848-1854), the overall balance of creating a body of qualiied oficers was not satisfactory. However, the reading of the Military Manuals, combined with military experience, contributed to a quite competent military training, with professional nuances. Thus, the historiographical thesis that points to the absence of a professional armed force in the irst half of the 19th century, because of the lack of a technical school, becomes relative, given that it disregards that military training –as it came to pass in other regions- was carried out through informal educational pathways which are more dificult to trace.